(untitled) (International conference on multidisciplinary science, 2026)
This study focuses on the methodology of fostering ecological awareness in primary school students through interdisciplinary integration. By combining subjects such as natural sciences, language arts, mathematics, and visual arts, environmental concepts can be conveyed to young learners in a systematic and meaningful way. Linking theoretical knowledge with practical observations, creative projects, and interactive activities not only develops students’ ecological understanding but also enhances critical thinking, problem-solving skills, and a sense of responsibility toward nature.